Optimalisasi Fungsi Taman Pustaka dalam Menunjang Pembelajaran Pendidikan Agama Islam di SD Negeri 050640 Desa Kaperas Kec. Kutambaru Kab. Langkat - Muhammad Najari; Baron Irvani; Rogayya Tusakdiyah (Medan Resource Center, 2021)
This research aims to identify how the steps of Islamic religious education teachers in optimizing the use of school bibliotek as learning resources in supporting PAI education. This research is a descriptive qualitative research type. Descriptive qualitative research is not intended to test certain hypotheses, but only describes what conditions exist. The author uses the procedures for documentation, interviews, and observations in collecting information in the field. The results of this research show that: (1) Taman Pustaka SD Negara 050640 in Kaperas Village has functioned well as a provider of learning resources for students in helping to achieve PAI educational goals, (2) Taman Pustaka as a supporter of Islamic learning education in State Junior High School 4 Binjai can be seen from the forms of using bibliotech as a source of Islamic Religious Learning education, (3) Optimization of school libraries in supporting Islamic learning education at State Elementary School 050640 in Kaperas Village is tried by procuring collections through purchases, gifts and donations, processing library materials through tasting, inventory, classification and cataloging of library materials.